Reinforcement of Concrete Shoring Systems by Prestressing. (23rd September 2022) - Mekdash, Hani; Jaber, Lina; Temsah, Yehya; Sadek, Marwan
Abstract : Reinforced concrete piles are useful structural elements to support deep excavations. A pile wall is usually supported by one or several rows of anchors, depending on the depth of the excavation and the nature of the soil retained. The purpose of this work is to investigate the efficacy of posttensioned piles in retaining a 10.0 m deep excavation without using tieback anchors. In addition to the conventional passive steel reinforcement, the piles in this system include steel strands placed eccentrically in their sections, and they are referred to as posttensioned piles. The performance of posttensioned piles is investigated using the finite element modeling software PLAXIS 2D. The results are experimentally validated on a large-scale construction site. The horizontal displacement of posttensioned piles in a 10 m deep excavation was found to be within allowable limits with a 7.36% difference in the horizontal displacement of pile top at the final excavation level in PLAXIS 2D. In terms of cost, PTP is executed at 35% cost less than the conventional reinforced method.